Antibacterial Activity and Chemical Composition of Popular Plant Essential Oils and Their Positive Interactions in Combination - Mráz, Petr; Kopecký, Marek; Hasoňová, Lucie; Hoštičková, Irena; Vaníčková, Alena; Perná, Kristýna; Žabka, Martin; Hýbl, Marian (Molecules (Basel, Switzerland), 2025)
Bacterial diseases are a global problem that threatens human health and cause many deaths each year. The alarming rise in bacterial resistance to modern antimicrobials is particularly concerning. In practice, this necessitates increasing the dosage of antimicrobial agents, posing a potential risk of adverse effects on human health. Additionally, the development of antibiotic resistance is one of the main factors contributing to the ever-growing costs of the global healthcare system. For these reasons, natural and safe antimicrobial agents are increasingly sought after. In this study, the antibacterial activity of 31 different essential oils (EOs) was investigated against Escherichia coli and Staphylococcus aureus. The most effective EOs were further tested both individually and in dual combinations. Minimum inhibitory concentrations (MICs) and fractional inhibitory concentrations (FICs) were determined to reveal synergistic effects, suggesting potential practical applications. The main bioactive compounds of the EOs with the highest inhibitory activity were identified and quantified using GC-MS/MS analysis. Of the tested EOs, seven demonstrated a strong antimicrobial effect against E. coli, most notably oregano (MIC 128 µg/mL) and the thyme/oregano combination (MIC 64 µg/mL, FIC 0.75), while thirteen were effective against S. aureus, most notably oregano and garlic (MIC 128 µg/mL),and the pelargonium/garlic combination (MIC 32 µg/mL, FIC 0.375). The pharmaceutical, agricultural, and food industries are promising fields for the application of these safe and natural antimicrobial agents, offering a new range of solutions to combat serious bacterial pathogens.
Keywords: Drug Synergism; Oils, Volatile; antibakteriální látky; synergismus léků; essential oil/GC-MS/MS; fractional inhibitory concentration; Microbial Sensitivity Tests; Plant Oils; oleje rostlin; minimal inhibition concentration; lidé; Escherichia coli; Anti-Bacterial Agents; oleje prchavé; Staphylococcus aureus; Humans; mikrobiální testy citlivosti